Punishment as defined by the Criminal Code of the Russian Federation and the Russian criminal law doctrine: Concept, system, and classification - L.R. Safin (Ученые записки Казанского университета: Серия Гуманитарные науки)
This article outlines the core tenets of the Russian criminal law doctrine in treating punishment as a means of prosecution. With an account of the inconsistent interpretations of punishment offered by Russian criminal law scholars, a critical analysis of its legislative definition was carried out. A special focus was laid on the key features of the list of punishments set out in the Criminal Code of the Russian Federation as a legally established and hierarchically ordered system of criminal penalties for deciding on the nature and intricacies of the defendant’s criminal liability, as well as possible commutation and remission. With this approach, certain types of punishment can be studied for their specific character and classified on various grounds delineated in the Criminal Code of the Russian Federation and professional literature. The obtained results also shed light on such a topical issue of today’s Russian criminal policy and procedure as how to distinguish between different types of punishment that imply no social exclusion.